Ground Deformation After a Caldera Collapse: Contributions of Magma Inflow and Viscoelastic Response to the 2015–2018 Deformation Field Around Bárðarbunga, Iceland. Issue 3 (12th March 2021) - Li, Siqi; Sigmundsson, Freysteinn; Drouin, Vincent; Parks, Michelle M.; Ófeigsson, Benedikt G.; Jónsdóttir, Kristín; Grapenthin, Ronni; Geirsson, Halldór; Hooper, Andrew; Hreinsdóttir, Sigrún
Abstract: Improvement of our understanding of the role of ground deformation due to viscoelastic relaxation following eruptions is important, as the generated signals can resemble renewed magma inflow. We study post‐eruptive unrest at the subglacial Bárðarbunga volcano, Iceland, after a caldera collapse and major magma drainage in 2014–2015. Elevated seismicity began about 6 months after the eruption ended, including nine M lw > 4.5 earthquakes. Global Navigation Satellite System and Sentinel‐1 Interferometric Synthetic Aperture Radar geodesy are applied to evaluate post‐eruptive ground deformation from 2015 to 2018. Horizontal velocities locally exceed 10 cm/year and rapidly decay with distance away from the caldera. We explore two end‐member models and their combination to explain the post‐eruptive deformation field: 1) viscoelastic relaxation caused by the co‐eruptive caldera collapse and magma withdrawal, and 2) renewed magma inflow. We find parameter combinations for each model that explain the observed ground deformation. The purely viscoelastic relaxation model, consisting of a half‐space composed of a 7‐km thick elastic layer on top of a viscoelastic layer with a viscosity of 3.0 × 10 18 Pa s reproduces broadly the observations. A simple magma inflow model consisting of a single point source with an inflow rate of 1 × 10 7 m 3 /year at 0.7 km depth broadly fits the observations, but may be unrealistic. A more elaborate model of magma inflow into a 10‐km deep sill combined with slip on the caldera ring fault explains the observations well. Our results suggest that the co‐eruptive deformation field is likely influenced by viscoelastic relaxation, renewed magma inflow, or a combination of both processes. Key Points: Post‐eruptive inflation‐like volcano deformation signal can result from viscoelastic relaxation in response to eruptive events Deep magma inflow coupled with reversed slip on caldera faults can create deformation signal similar to that caused by shallow magma inflow Bárðarbunga post‐eruptive deformation field may be influenced by viscoelastic relaxation, renewed magma inflow or a combination of both